The use of cone beam computed tomography in endodontics (Part I). Analysis of root canal topography (Эндодонтия Today, 2020)
Saving teeth and maintaining their function are the main objectives of dentistry. Currently, an increasing number of patients are motivated by the fact that dentists have made every effort to save the tooth. Despite notable achievements of world and domestic implantology, endodontic treatment is still important in the treatment of periodontal diseases. The emergence of new tools and equipment has significantly improved the quality of endodontic treatment, but even the use of the microscope in endodontic practice has not reduced the importance of radiological diagnosis and treatment monitoring.